A Phase II Study of Biweekly Cisplatin, Fixed-Dose-Rate Gemcitabine and Infusional 5-Fluorouracil in Patients With Metastatic Pancreatic and Biliary Cancers. (February 2018) - Davis, Elizabeth J.; Griffith, Kent A.; Kim, Edward J.; Ruch, Joshua M.; McDonnell, Kevin J.; Zalupski, Mark M.
Abstract : Objectives: Combinations of gemcitabine, 5-fluorouracil (5-FU), and platinum have demonstrated improved outcomes compared with singlet chemotherapy in pancreatic and biliary cancers. This phase II study examined efficacy and safety of a novel schedule of cisplatin, fixed-dose-rate gemcitabine and infusional 5-FU. Materials and Methods: Patients with metastatic adenocarcinoma of the pancreas or biliary tract, previously untreated or having received 1 cytotoxic regimen for advanced disease, were treated with gemcitabine 1000 mg/m 2 intravenously (IV) over 100 minutes, cisplatin 35 mg/m 2 IV over 30 minutes, and 5-FU 2400 mg/m 2 IV over 48 hours on day 1 of a 14-day cycle. Patients were treated until disease progression or for 12 cycles. After 12 cycles, patients with stable or responding disease could continue gemcitabine and 5-FU. The primary endpoint was objective response. Results: Thirty-nine patients were treated: 8 with biliary cancer (all untreated) and 31 with pancreatic cancer (17 untreated, 14 previously treated). Best response in 25 untreated patients was partial response in 40%, stable disease in 40%, and progressive disease in 20%. In 14 previously treated pancreatic patients, best response was partial response in 7%, stable disease in 50%, and progressive disease in 43%. Median overall survival in untreated patients was 10.3 versus 4.9 months in previously treated patients. Adverse events were primarily uncomplicated hematologic toxicity, ≥grade 3 neutropenia (54%), anemia (21%), and thrombocytopenia (13%). Conclusion: Biweekly cisplatin, fixed-dose-rate gemcitabine, and infusional 5-FU demonstrated a high response rate and were well tolerated, encouraging further investigation of this regimen in metastatic pancreatic and biliary cancers.